Hip Arthroscopy in Patients Less than 25 Years of Age in the Treatment of Labral Tears: Aetiology and Clinical Outcomes. Issue 5 (September 2017) - Bayley, Gillian; Poitras, Stephane; Parker, Gillian; Beaulé, Paul E.
Background: Hip arthroscopy has evolved into a well-established and rapidly growing field of orthopedic surgery for the management of labral tears. The purpose of this study was to review clinical outcomes of patients less than 25 years of age undergoing hip arthroscopy for treatment of a labral tear. Methods: From 2005 to 2013, 82 hips in 76 patients with mean age of 20.4 (16-25 range) underwent hip arthroscopy for treatment of labral-chondral damage. The Western Ontario McMaster Universities Osteoarthritis Index (WOMAC) and hip disability and osteoarthritis outcome score (HOOS) were recorded at latest follow-up. Results: 36 of 86 hips (42%) had isolated labral pathology with no associated bony pathology (normal alpha and centre-edge angle; no retroversion). Beck score (intraoperative cartilage damage) of 3 or more was significantly associated with an alpha angle of more than 55 degrees (odds ratio [OR], 3.6; confidence interval [CI], 1.2-11.0) and presence of femeroacetabular impingement (OR, 4.5; CI, 1.3-15.2). HOOS pain, sports/recreation, and quality of life significantly improved from preoperative to one year after surgery (p<0.05). 8 patients had re-operations for persistent pain; 5 underwent arthroscopic labral repair; 2 underwent arthroscopy with subsequent periacetabular osteotomy (PAO); 1 had only a periacetabular osteotomy (PAO). Complications included 2 lateral femoral cutaneous nerve deficits and 1 deep vein thrombosis. Conclusions: Labral tears in patients less than 25 years of age occurs commonly without bony deformities, with those with normal head/neck contour demonstrating significantly less early cartilage damage than those with bony pathology. Hip arthroscopy in young patients can improve function and quality of life with minimal morbidity.